Geotechnologies in High School: Remote sensing as a tool for environmental education in the northeastern brazilian semiarid region (Research, Society and Development, 2025)
The advancement of digital technologies has driven transformations in education, demanding innovative pedagogical practices that integrate technological resources into teaching. In this context, remote sensing emerges as an effective tool for teaching Geography and fostering critical environmental awareness. This study analyzed the perception of high school students from the Pedro Falconeri Rios Full-Time State School, in Pé de Serra (Bahia) regarding ecological degradation of the caatinga and susceptibility to desertification in the Brazilian semi-arid region, through the implementation of a didactic sequence using remote sensing products. The research, descriptive and quantitative in nature, was organized into four stages: preparation, data collection, application of the sequence, and reflection. Data collected through questionnaires were analyzed using descriptive statistics. The results showed that the use of geotechnologies enhanced the development of spatial reading skills, map interpretation, and critical analysis of the interactions between society and nature. Students demonstrated understanding of degradation processes and identified the causes of desertification. It is concluded that remote sensing is an innovative and interdisciplinary educational resource that can integrate science, technology, and environmental education, promoting critical, contextualized, and sustainable learning.